Re-positioning SoTL toward the T-shaped Community - Eady, Michelle J.; Abrahamson, Earle; Green, Corinne A.; Arcellana-Panlilio, Mayi; Hatfield, Lisa; Namaste, Nina (Teaching and Learning Inquiry, 2021)
Amongst a range of changes that have taken place within tertiary education, perhaps the most revolutionary has been a shift to student-centred approaches focused on life-long learning. Accompanying this approach to holistic higher education (HE) has been a growing interest in, and understanding of, the Scholarship of Teaching and Learning (SoTL). SoTL has, at its core, a deep concern with student learning and is therefore well-aligned with higher education’s renewed focus on its students. In this conceptual paper, we examine the impact of the T-shaped person which many tertiary institutions are operationalizing to inform and connect the development of students’ deep disciplinary knowledge with non-academic and employment readiness skills (such as communication, problem-solving, teamwork, and critical thinking). Importantly, we argue for a re-positioning of SoTL to complement and support this model, with SoTL as both the fulcrum and the fluid, multiple threads of discourse that are intricately entwined around the structure of the T-shaped model. We encourage our colleagues to strive to be T-shaped practitioners and we cast a vision of a T-shaped community. Here, all stakeholders within HE connect both their academic knowledge and holistic skills in collaborative ways to produce learners who flourish in modern society. The SoTL community plays a pivotal role in achieving this vision and is well-positioned to expand the current notion of SoTL toward a more holistic, interconnected, central role in HE.